Development of zinc oxide-based diluted magnetic semiconductor thin films and nanostructures possessing room temperature ferromagnetism - Zhao, Xing (2013)
Spintronics has emerged as a new technology, which is based on electron spins rather than electron charges to carry information. Spintronics offers an opportunity for a new generation of devices combining standard microelectronics with spin-dependent effects that arise from the interactions between the spins of charge carriers and the magnetic properties of materials. In this project, pure ZnO thin films, Cu-doped ZnO thin films, Ni-doped ZnO thin films, pure ZnO nanostructures, and Co-doped ZnO nanostructures were developed as diluted magnetic semiconductor (DMS) materials for potential applications in spintronic devices. Annealing effect under varying conditions on the structural and magnetic properties of the ZnO-based DMS thin films was investigated. A lattice deviation of both as-deposited and annealed pure ZnO thin films was observed through X-ray diffraction (XRD), which was attributed to oxygen vacancies and interstitial Zn in the films. Significant diffusion of O from the bottom to the top surface of the films occurred during annealing in Ar and air as revealed by X-ray photoelectron spectroscopy (XPS), which resulted in increased oxygen vacancies in the films after annealing. Furthermore, prolonged annealing could promote the diffusion of O and induce more oxygen vacancies in the films. Both the as-deposited and the annealed pure ZnO thin films displayed diamagnetism at room temperature, though the oxygen vacancies existed in all the films, indicating that the oxygen vacancies were necessary while only oxygen vacancies were not enough to induce room temperature ferromagnetism (RTFM) of ZnO-based DMS. For the Cu-doped ZnO thin films, significant diffusion of O and Cu from the bottom to the top surface of the films was observed after annealing in Ar or air through XPS. Reduction of Cu occurred in the films annealed in Ar, while oxidization of Cu occurred in the films annealed in air. Extended annealing in air made a higher concentration of oxygen vacancies in the films, and also increased the amount of Cu2+ at Zn2+ sites of ZnO wurtzite lattice. The as-deposited Cu-doped ZnO thin film displayed RTFM that originated from Cu2+ based on the bound magnetic polaron (BMP) model. However, RTFM disappeared in the films annealed in Ar due to the disappearance of Cu2+. Extended annealing of the Cu-doped ZnO films in air enhanced the saturation magnetization (Ms) of the films, which was attributed to a stronger BMP effect. For the Ni-doped ZnO thin films, oxidization of metallic Ni to Ni2+ occurred in the film annealed in air at 600 °C, while reduction of Ni2+ to its metallic state occurred in the film annealed in Ar at 600 and 800 °C. In addition, there appeared to be significant diffusion of Ni from the bottom to the top surface of the film during annealing in Ar at 800 °C. Both as-deposited and annealed Ni-doped ZnO films displayed obvious RTFM which was from metallic Ni, Ni2+ or both with two distinct mechanisms. Furthermore, a significant improvement in Ms in the films was observed after annealing in air or Ar at 600 °C compared to that in the as-deposited film. An even higher Ms value was observed in the film annealed in Ar at 800 °C compared to that at 600 °C mainly due to the diffusion of Ni. The ultraviolet emission of the Ni-doped ZnO thin film was restored during annealing in Ar at 800 °C, which was also attributed to the diffusion of Ni. Pure ZnO microrod arrays with different topographies were grown on bare silicon substrates through an electrochemical deposition method with varying potentials from -0.8 to -2.0 V. When the potential was -2.0 V, pure ZnO needle-shaped microrod arrays were formed. The applied potential played a key role in the nucleation and growth processes of the pure ZnO microrod arrays. Zn was in its two-valence oxidation state in the pure ZnO microrods grown with -0.8 V, while it was in its minor metallic and major two-valence oxidation states concurrently in the pure ZnO microrods grown with -1.2, -1.6, and -2.0 V. The reduced metallic Zn was doped into the interstices of ZnO wurtzite lattice and become interstitial metallic Zn. Furthermore, the concentration of interstitial metallic Zn increased in the pure ZnO microrods with the decreased potential. Diamagnetism was displayed by the pure ZnO microrod arrays grown with -0.8 V, while RTFM could be displayed by the pure ZnO microrod arrays grown with -1.2, -1.6, and -2.0 V. In addition, more negative potentials significantly enhanced the Ms of the pure ZnO microrod arrays. The RTFM in the pure ZnO microrod arrays could be attributed to the interstitial metallic Zn. Diamagnetic pure ZnO nanorod arrays were formed on the silicon substrate with a ZnO seed layer through a chemical deposition method, while ferromagnetic Co-doped ZnO nanorod and microsphere arrays were synthesized on bare silicon substrates via an electrochemical deposition method, illustrating that the electrochemical deposition method rather than the chemical deposition method was capable of doping Co into ZnO matrix under a negative potential to synthesize Co-doped ZnO nano/micro structures with RTFM. The RTFM of the Co-doped ZnO nanorod and microsphere arrays could be properly interpreted using the BMP model.